Analisis Investasi dan Kelayakan Ekonomi Penambangan Emas di PT DEF Kecamatan Simpenan, Kabupaten Sukabumi, Provinsi Jawa Barat - Satrio Aji Harmadi; Zaenal; Sriyanti (UNISBA Press, 2022)
Abstract. PT. DEF is a company that will plan gold mining in Simpenan District, Sukabumi Regency, West Java Province which needs to be done investment analysis and economic feasibility of mine to see gold reserve prospect in that location. Reference to the preparation of economic model used based on investment cost, production cost, and income from bullion gold sales. To consider this, an economics analysis is required based on the concept of discounted cash flow analysis and sensitivity analysis. The parameters used to determine economic viability in bullion gold production of PT. DEF are Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PBP) and sensitivity to NPV value due to changes in selling price and production cost. Discounted Cash Flow Analysis Rate of Return (DCFROR) is an investmentrelated analysis that takes into account the time value of money and discount rate calculated by the Weighted Average Cost of Capital method of 10,44%. Cash flow is calculated per year with the objective of evaluation determined through Cash Outlow reduction from Cash Inflow resulting from investment activity. Based on analysis result of DCFROR analysis, Net Present Value value is Rp Rp73.474.877.956, Internal Rate of Return is 89.56 %, with Payback Period is 1 year 2.64 months, then this project is feasible to run. The parameters of investment that become the sensitivity are production cost and selling price. Assessment of sensitivity to NPV value due to changes in selling price and production cost at PT. DEF assuming escalation of revenues and cost escalation by 2% until 50% and so that the value of Net Present Value generated can show how sensitive the value obtained from the parameters of selling price. When the selling price drops above 16% and the production cost rises above 48%, then the project will be a loss. Abstrak. PT DEF merupakan perusahaan yang melakukan penambangan emas di Kecamatan Simpenan, Kabupaten Sukabumi, Provinsi Jawa Barat, yang perlu dilakukan analisis investasi dan kelayakan ekonomi tambang untuk melihat prospek cadangan emas. Acuan penyusunan model ekonomi yang digunakan berdasarkan biaya investasi, biaya produksi, dan pendapatan dari penjualan bullion emas. Untuk mempertimbangkan hal tersebut maka diperlukannya analisis keekonomian berdasarkan konsep aliran kas diskonto (discounted cash flow analysis) dan analisis sensitivitas. Parameter yang digunakan untuk menentukan kelayakan ekonomi dalam produksi emas PT. DEF adalah Net Present Value (NPV), Internal Rate of Return (IRR), Payback Periode (PBP) dan sensitivitas terhadap nilai NPV akibat perubahan harga jual dan biaya produksi. Analisis Discounted Cash Flow Rate of Return (DCFROR) merupakan analisis yang berhubungan dengan investasi yang memperhitungkan nilai waktu dari uang dan discount rate yang dihitung dengan metode Weighted Average Cost of Capital yaitu 10,44%. Aliran kas dihitung pertahun dengan tujuan evaluasi yang ditentukan melalui pengurangan Cash Outlow dari Cash Inflow yang dihasilkan dari kegiatan investasi. Berdasarkan hasil pengkajian analisis DCFROR didapat nilai Net Present Value yaitu Rp73.474.877.956, Internal Rate of Return yaitu 89,56 %, dengan Payback Periode yaitu 1 tahun 2,64 bulan, maka proyek ini layak untuk dijalankan. Parameter investasi yang menjadi sensitivitas yaitu biaya produksi dan harga jual. Penilaian sensitivitas terhadap nilai NPV akibat perubahan harga jual dan biaya produksi di PT. DEF dengan asumsi eskalasi pendapatan sebesar 2% hingga 18% serta eskalasi biaya sebesar 2% hingga 50% sehingga nilai Net Present Value yang dihasilkan dapat menunjukan seberapa sensitif nilai yang didapatkan dari parameter harga jual. Ketika harga jual menurun diatas 16% dan biaya produksi naik diatas 48%, maka proyek ini akan rugi.